Compact High-Gain Dual-band Patch Antenna With Dielectric Superstrate for Wi-Fi 6 Applications - Muangrung, Bhuwakorndit; Lang, Alongkorn; Torrungrueng, Danai; Phongcharoenpanich, Chuwong; Kawdungta, Supakit (My University, 2023)
The compact high-gain dual-band double circular patch antenna with dielectric superstrate is introduced for Wi-Fi 6 applications. The double circular patch antenna can be operated at two frequency bands of 2.41-2.54 GHz and 4.94-6.03 GHz. The dielectric superstrate and parasitic patches are employed in front of the antenna to enhance the antenna gain. From simulated results, the dielectric superstrate and parasitic patches can improve the antenna gain. The proposed antenna has |S11| less than-10 dB in both operating frequency bands, unidirectional radiation pattern, and gain of 4.8 dBi at 2.45 GHz and 4.57 dBi at 5.5 GHz.
Keywords: Dielectric superstrate; Dual-band; Patch Antenna; Wi-Fi 6